Legal Analysis of the Protection and Legal Certainty of Electronic Land Certificates as an Instrument of Land Reform in Indonesia - Muhammad Iqbal, Fariz (KRTHA BHAYANGKARA, 2025)
Electronic land certificates serve as a solution for the reform of the land system in the digital era. However, challenges related to legal protection and certainty remain the main issues, particularly in how the electronic land certificate system can be integrated with the legal system and how the rights of the public can be safeguarded. The primary objective of this research is to examine the aspects of legal protection and certainty of electronic land certificates and the impact of their implementation on the efficiency of the land system in Indonesia. The research adopts a normative juridical approach, utilizing secondary data sources. The legal protection and certainty of electronic land certificates in Indonesia are ensured through a system that uses cryptographic technology and electronic signatures, which guarantee authentication, integrity, and data security, providing legal certainty equivalent to physical land certificates for rightful landholders. The implementation of electronic land certificates in Indonesia has a significant positive impact on the efficiency of the land system, facilitating and accelerating the processes of registration, verification, and the issuance of certificates digitally.